Factors correlated with treasury bond spreads in an emerging capital market - Cheng, Fan Fah; Syed Mohamed, Mohamed Ariff (Center for Promoting Ideas, 2011)
This paper identifies macroeconomic and financial factors that are significantly correlated with Treasury bond term spreads observed over a quarter century in an emerging capital market, Malaysia. We adapted the very popular arbitrage pricing model approach widely used in share market studies and used ten macroeconomic and financial factors pre-specified to study the bond pricing behavior in this market, where industry statistics suggest that this market is the fourth largest bond market in Asia. Our findings suggest that trade balance, industrial production, GDP growth rate, money supply and the amount of funds raised are correlated with the term spreads. Trade balance is very proper to be a key variable since this emerging economy is among the top - 8 trading countries with international trade constituting over 200 percent of GDP. These results, being a first using the arbitrage pricing model, help add to our understanding of bond pricing dynamics in one emerging market.